Monitoring Water Quality Using Biotic Indices of Benthic Macroinvertebrates along Surfaces Water Ecosystems in Some Tourism Areas in East Java, Indonesia - Wimbaningrum, Retno; Indriyani, Serafinah; Retnaningdyah, Catur; Arisoesilaningsih, Endang (Graduate School, Universitas Brawijaya, 2016)
The research aimed to monitor surface water quality by using water quality index NSF-WQI and accurate biotic index of benthic macroinvertebrate. This study was conducted in September to November 2012 in some water tourism destinations in three regencies, i.e. Jember (three sites), Pasuruan (one site), and Malang (one site), East Java, Indonesia. Each site consisted of three stations (upstream, middlestream and downstream). Reference upstream and middlestream were located in the Meru Betiri National Park (MBNP) Jember. Water quality and benthic macroinvertebrates sampling were conducted in each site. While physical-chemical data consisted of TDS, DO, pH, NO3-N, TP and temperature were analyzed to determine the NSF-WQI index. Macrozoobenthic data were analyzed to determine three diversity indices and 11 biotic indices. Results showed that based on parameter of DO, TP, NO3-N, TDS and pH, water quality in downstreams were generally lower than upstreams. Upstream to middlestreams of two sites in Jember were good to excellent based on NSF-WQI water quality and biotic indices. Therefore, the water were qualified as drinking water resources and also served as safe recreational water. The accurate biotic indices to surface water quality in this study were % EPT, ASPT, HBI, FBI and % Gastropodes.Keywords: biotic indices, benthic macroinvertebrates, water quality index, water tourisms destination